2021
DOI: 10.1007/s10530-020-02445-9
|View full text |Cite
|
Sign up to set email alerts
|

Coastal ocean acidification and nitrogen loading facilitate invasions of the non-indigenous red macroalga, Dasysiphonia japonica

Abstract: Coastal ecosystems are prone to multiple anthropogenic and natural stressors including eutrophication, acidification, and invasive species. While the growth of some macroalgae can be promoted by excessive nutrient loading and/or elevated pCO2, responses differ among species and ecosystems. Native to the western Pacific Ocean, the filamentous, turf-forming rhodophyte, Dasysiphonia japonica, appeared in estuaries of the northeastern Atlantic Ocean during the 1980s and the northwestern Atlantic Ocean during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…anophagefferens action. Our results suggest that the recent invasion of D. japonica in NY estuaries (Young and Gobler 2021), especially in Great South Bay, may be influencing the patterns of brown tide occurrence, potentially causing shorter and less intense blooms. Finally, the strategic deployment of G. tikvahiae as an element of open-water coastal aquaculture systems may be an environmentally friendly and revenue-generating option for preventing and/or controlling blooms caused by A. anophagefferens and likely other harmful algae.…”
Section: Great South Bay Brown Tide Experimentsmentioning
confidence: 85%
See 2 more Smart Citations
“…anophagefferens action. Our results suggest that the recent invasion of D. japonica in NY estuaries (Young and Gobler 2021), especially in Great South Bay, may be influencing the patterns of brown tide occurrence, potentially causing shorter and less intense blooms. Finally, the strategic deployment of G. tikvahiae as an element of open-water coastal aquaculture systems may be an environmentally friendly and revenue-generating option for preventing and/or controlling blooms caused by A. anophagefferens and likely other harmful algae.…”
Section: Great South Bay Brown Tide Experimentsmentioning
confidence: 85%
“…This picoplankton achieves high densities within the open waters of estuaries, but its cell concentrations decline by orders of magnitudes in shallow tributaries where salinities are not significantly different from neighboring, open estuarine sites (SCDHS 1990(SCDHS -2020; a major difference between these environments is the presence of much higher densities of seaweeds in the tributaries (Tang and Gobler 2011). In addition, D. japonica has recently invaded the same south shore lagoons that host brown tides cause by A. anophagefferens (Young and Gobler 2021), and since this invasion has been documented (2018), brown tides in these lagoons have been less intense (10 5 cells mL −1 vs. 10 6 cells mL −1 ) and shorter in duration (weeks vs. months) compared to before the invasion (SCDHS 1990(SCDHS -2020. As such, it is possible that macroalgae influence the occurrence of brown tides in NY estuaries.…”
Section: Great South Bay Brown Tide Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been confirmed that some species of Gracilaria native to Asian seas limit the formation of numerous HABs by allelopathy [186,188,189]. Dasysiphonia japonica grows faster than other red macroalgae, which helps it compete with other types of algae in nutrient-rich estuaries [190]. No research has been conducted on the possible impacts of D. japonica on HABs phytoplankton, including A. anophagefferens [191].…”
Section: Biologicalmentioning
confidence: 99%